Determinants of Health-Related Quality of Life in Schizophrenia: Beyond the Medical Model - Lim, Madeline W. Z.; Lee, Jimmy (Frontiers in Psychiatry, 2018)
Background: Improving Quality of Life (QoL) in Schizophrenia is an important treatment objective in the shift towards person-centred and recovery-oriented care. Health-Related Quality of Life (HRQoL) is a focused aspect of QoL that is directly impacted by healthcare intervention. This aim of the current study was to ascertain the clinical determinants of HRQoL in Schizophrenia and their collective contribution to HRQoL. Methods: 157 stable outpatients with schizophrenia were recruited for this study. Data collected included sociodemographic information and clinical characteristics. HRQoL was assessed on the RAND-36. Psychopathology was assessed on the Positive and Negative Syndrome Scale (PANSS) and functioning measured on the Global Assessment Scale (GAS). Findings: Multiple regression revealed that the Physical Health Component (PHC) of the RAND-36 was associated with positive symptoms (beta=-0.218, p=0.005) and presence of psychiatric comorbidity (beta=-0.215, p=0.003). The Mental Health Component (MHC) was associated with depressive (beta=-0.364, p<0.001) and positive (beta=-0.175, p=0.021,) symptoms. Symptoms, functioning, presence of psychiatric comorbidities, gender and age account for 20.3% of the total variance observed in HRQoL. Conclusion: Depressive and positive symptoms are key clinical determinants of HRQoL in people with schizophrenia. However, the medical model – looking solely at clinical determinants - could not account for a large proportion of variance in HRQoL. Hence, future research beyond the medical model is required to uncover the determinants of HRQoL in Schizophrenia. Identifying these factors will contribute towards developing a holistic and person-centered management plan for people with schizophrenia.